2012
DOI: 10.12693/aphyspola.122.202
|View full text |Cite
|
Sign up to set email alerts
|

Toward Finding a Commercial Method for Deposition of Nanostructured SnO2Thin Films

Abstract: Nanostructured tin oxide (SnO2) thin lms have been prepared by spray pyrolysis technique. The eects of deposition conditions such as substrate temperature and tin chloride concentration in the precursor solution on physical properties of lms have been investigated. The physical characterization of samples was carried out by UV-VIS spectroscopy, X-ray diraction, scanning electron microscopy, and the Hall eect experiment for optical, structural, morphological and electrical studies, respectively. The lms are pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
3
3
Order By: Relevance
“…These observations are well consistent with those reported previously by Joseph et al [33] but contradictory to the results that have been reported by Memarian et al [32] and Maleki et al [34]. Conversely, lower deposition temperature implies higher density of grain boundaries and consequent higher concentration of structural defects such as point defects (e.g.…”
Section: Optical Properties By Optical Spectroscopic Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…These observations are well consistent with those reported previously by Joseph et al [33] but contradictory to the results that have been reported by Memarian et al [32] and Maleki et al [34]. Conversely, lower deposition temperature implies higher density of grain boundaries and consequent higher concentration of structural defects such as point defects (e.g.…”
Section: Optical Properties By Optical Spectroscopic Analysissupporting
confidence: 87%
“…[37,38]), but it is inconsistent with other published works (e.g. [32,39,40]). However, the preferred growth orientation is significantly controlled by the deposition parameters (deposition temperature [41], film thickness [42], doping concentration [40], etc).…”
Section: Phase Identification and Evolution By Xrdcontrasting
confidence: 59%
See 1 more Smart Citation
“…The sheet resistances of our films are between 205.27 Ω and 325.25 Ω, which are consistent with the reported values of sheet resistance obtained for SnO 2 prepared by spray pyrolysis technique. [35] The resistivity values of SnO 2 films are calculated from the following formula:…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The second solution (doped) uses the initial composition of the first solution with the added doping of as much as 2 wt% fluor (F) by dissolving 0.24 grams of NH 4 F with 0.56 ml of distilled water. This solution was dropped carefully by using a pipette to prevent solution turbid (Memarian & Rozati, 2012). …”
Section: Precursor Mixingmentioning
confidence: 99%